Sodium butyrate impedes the lymphoma caused by Marek’s disease virus via regulating the mitochondrial apoptosis pathway - Lin, Qiaoer; Zhou, Jun; Yang, Fan; Zheng, Congsen; Chen, Meiting; Chang, Chuanzhe; Cai, Shikai; Wen, Feng; Wang, Nina; Chen, Yanfeng; Qin, Limei (Frontiers in Veterinary Science, 2024)
Sodium butyrate (NaB) has garnered attention in recent years for its ability to impede the malignant progression of tumors. In order to explore the potential inhibitory effects of NaB on the replication of Marek's disease virus (MDV) and subsequent lymphoma formation, newly hatched chickens were infected with the vvMDV Md5 strain and administered NaB prior to (prevention group) or following (treatment group) Md5 inoculation. The results revealed that NaB played a pivotal role in diminishing both the incidence and fatality rates in chickens afflicted with Md5 infection. Notably, NaB exhibited a remarkable capacity to inhibit the expression of MDV immediate early genes, i.e.ICP4 and ICP27, thus attenuating tumorigenesis in the chicken spleen. To further elucidate the mechanism of NaB on lymphoma cells, MDV bearing lymphoma cells, i.e. MSB-1 were exposed to NaB for 24 hours prior to various experimental tests. The results revealed that NaB effectively hindered the proliferation, migration, and colony formation of MSB-1 cells. Furthermore, NaB demonstrated the ability to modulate the key molecules in mitochondrial apoptosis pathway. Taken together, these findings reveal that NaB can impede the lymphoma caused by MDV via regulating the mitochondrial apoptosis pathway, both in vitro and in vivo.